Handbook of Inpatient Cardiology - Wells, Bryan J.; Quintero, Pablo A.; Southmayd, Geoffrey (Springer International Publishing : Imprint: Springer, 2020)
This book serves as a pocket-sized resource to aid with the diagnosis and management of cardiovascular disease in the inpatient setting. Containing up-to-date information from guidelines and clinical trials, this book is the only handbook-style reference on cardiac care designed specifically for the hospitalist. The first section of the book covers cardiac pathology with an emphasis on evidence-based and guideline-based approaches to patient care. Each chapter focuses on a specific cardiovascular disease state such as acute coronary syndrome, atrial fibrillation, pulmonary hypertension, and aortic disease. The second section examines the differential diagnoses and recommended workup for common cardiac chief complaints including chest pain, palpitations, syncope, and dyspnea. The third and final section discusses indications and interpretation of commonly used cardiac procedures and imaging modalities. This book provides a concise review over a broad range of cardiovascular disease states in an accessible handbook-style to aid with the care of these patients. The Handbook of Inpatient Cardiology is an essential resource for physician hospitalists caring for cardiac patients on the medical ward in addition to cardiology physicians and trainees, affiliate providers, and students.